A parametric investigation of castor oil (Ricinus comminis L) extraction using supercritical carbon dioxide via response surface optimization - Danlami, Jibrin Mohammed (Elsevier, 2015)
The optimal conditions of oil yield from castor (Ricinus communis L) seed using supercritical CO2 as extracting solvent were studied. Response surface methodology (RSM) was employed to show explicitly the influence of the process parameters such as temperature, pressure and the CO2 flow rate on the oil yield using BoxBehnken design. The linear terms of pressure, CO2 flow rate and temperature and the quadratic terms of temperature, pressure and CO2 flow rate, had a significant effect on the oil yield. The maximum oil yield obtained from the mathematical model was predicted to be 9.29% under the conditions of temperature 63.72 degrees C and pressure 29.90 MPa with CO2 flow rate of 4.15 mL/min. The fatty acid constituents of the seed oil extracted using supercritical CO2 were determined by gas chromatography-mass spectrometry (GC-MS) and Fourier transform infrared spectrometer (FTIR). Palmitic, stearic, oleic, linoleic, linolenic and ricinoleic acids were identified by GC-MS analysis after the formation of fatty acid methyl ester (FAME).